Preferred Sources of Information, Knowledge, and Acceptance of Automated Vehicle Systems: Effects of Gender and Age - Greenwood, Pamela M.; Baldwin, Carryl L. (Frontiers in Psychology, 2022)
Automobile crashes are a leading cause of death in the United States and worldwide. Driver automation systems and active safety systems have the potential to improve the safety and mobility of all road users and may particularly benefit older adults who have been slow to accept and adopt such systems. Age-related sensory-cognitive changes contribute to higher crash rates and increased physical frailty makes severe injury or death more likely when a crash occurs. Vehicle automation can decrease the sensory-cognitive load of the driving task and many advanced automated safety features can decrease crash severity. Acceptance and adoption of driver automation systems is necessary for their benefit to be realized yet little is known about drivers’ preferred sources of information and knowledge about such systems. In a sample of 404 active drivers, we examined the impact of age and gender on understanding and acceptance of vehicle automation, acceptance of new technologies more generally, and preferred sources of information to learn about vehicle automation. Results revealed that older respondents and females felt less technically sophisticated than their younger and male counterparts. Males subjectively reported greater understanding of vehicle automation. However, assessment of objective knowledge of automation operation showed males had no greater knowledge than females. Males also reported a greater willingness to accept higher levels of vehicle automation than females across all age groups. When asked how they would prefer to learn about new vehicle automation, older adults reported wanting information from more objective sources than their younger counterparts and were significantly less likely to rely on friends and family, or social media. The present results provide support for the idea that people are not willing to accept technology that they do not feel they understand well and conversely, if people feel that they understand vehicle automation they will be more likely to adopt it. The results provide insights into assisting drivers to gain more accurate knowledge and hence acceptance of vehicle automation systems.